Efektivitas Berbagai Macam Fitur Google Sebagai Media Pembelajaran Program Studi Pendidikan Ekonomi - Endah Andayani (Jurnal Penelitian dan Pendidikan IPS, 2021)
Abstract – The use of technology and information in the Covid-19 pandemic has affected learning methods in the network. The Google Classroom (GCR) application is considered an online learning medium that is time efficient and without being tied to learning in the classroom. At the beginning of the pandemic, the implementation of GCR which actually had various good features but was not yet fully understood and practiced by lecturers, this became the researcher's thinking whether GCR was effective in supporting the achievement of student competencies set out in the curriculum. This study aims to determine the effectiveness of using various Google features, namely GCR, Google Docs, Google Sheets, and Google Slides. The type of research used is descriptive qualitative by giving questionnaires to 15 students of economic education class 2017 and 5 lecturers who use the application. The results show that lecturers and students have used Google classroom effectively and are very supportive of learning. Google Docs is used only by one lecturer and 12 students, they use google docs because it can be accessed anywhere and can be accessed by more than one person. Google Sheets have not been used by all respondents, lecturers and students, because they use Microsoft Excel more often. Google Slides is only used by one lecturer and 13 students, Google Slides helps with online presentations. In the future, it is hoped that there will be more users of the Google feature to facilitate the work of both lecturers and students.